The Influence Of Online Learning Media On Student’ Interest In Learning In Class B Of Unimed Economics Education - Mica Siar Meiriza; Tamaria Br Sidebang; Ginting, Renata Olivia; Novita Sari Br Kaban; Eva Juli Yanti Situmorang; Ngiw Aman Harja (Outline Publisher, 2024)
This journal reviews the influence of online learning media on the learning interest of class B students in Unimed Econonics Education. In this research, data collection methods were used using questionnaires. The questionnaire was distributed to 30 sources appointed by the author. From students who are currently carrying out the online learning process and student responses to several questions created by researchers. From the diagram created by the researcher, it is clear that the dominant answer from students is that they do not agree and it can be proven that students do not like online learning and it makes it difficult for them to learn or understand the material. The application of online learning media is expected to determine students’ interest in learning in the economics education study program at Medan State University.